Behavior of Male and Female C57BL/6J Mice Is More Consistent with Repeated Trials in the Elevated Zero Maze than in the Elevated Plus Maze - Tucker, Laura B.; McCabe, Joseph T. (Frontiers in Behavioral Neuroscience, 2017)
The elevated plus maze (EPM) and elevated zero maze (EZM) are behavioral tests that are widely employed to assess anxiety-like behaviors in rats and mice following experimental manipulations, or to test the effects of pharmacological agents. Both tests are based on approach/avoidance conflict, with rodents perceived as “less anxious” being more willing to explore the brighter, open and elevated regions of the apparatus as opposed to remaining in the darkened and enclosed regions. The goal of this research was to compare, under identical laboratory conditions, the behavior of male and female C57BL/6J mice in EZM and EPM during repeated trials. Mice were tested either daily or weekly, exclusively in the EPM or EZM, for a total of five exposures. During the first trial, the mazes were explored equally as measured by the total distance traveled during the test session. However, mice tested in the EZM spent nearly twice the amount of time in the anxiogenic regions (open quadrants) as the mice tested in the EPM spent in the open arms of that apparatus. After the first trial in the EPM, amounts of ambulation and percent time in the open arms decreased significantly (independent of inter-trial interval) which has been well-described in previous research as the one-trial tolerance phenomenon. In contrast, behavior in the EZM remained comparatively stable for several trials when the animals were tested weekly or daily. Sex differences were limited to activity levels, with females being more active than males. In conclusion, the design of the EZM encourages greater exploration of the anxiogenic regions of the apparatus, and may also be a more suitable test than the EPM for experimental designs in which assessment of anxiety-related behaviors is needed at more than one time point following experimental manipulations.